Perancangan Video Profile Yayasan Sosial Kristen Salib Putih Salatiga - Widyatama, Billy Gracia; Tumimomor, Anthony Y.M. (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2024)
The Salatiga White Cross Christian Social Foundation is a social institution that focuses on social and humanitarian services, apart from that, this foundation also develops human resources through several programs. The foundation is a continuation of the services of the Witte Kruis Kolonie which was founded on 14 May 1902. The social services provided by this foundation include nursing homes, orphanages, work centers, work training centers, and medical centers. The large operational costs are one of the obstacles experienced by foundations in carrying out their services. Helping hands from donors are needed, but the use of media is currently not effective for donors or the public who want to know about the social services carried out by the White Cross Candidate Foundation. Based on the existing problems, information media is needed that can describe the vision, mission, and objectives of the foundation and provide a clear and detailed picture of what service areas are managed by the management of the White Cross Foundation. By using qualitative research methods and applying a linear strategy as a creative stage, it is hoped that we will be able to produce profile videos that can present foundation profile information in more detail and interest to potential donors or the general public who have an interest in social services. Keywords: Social Services, Salatiga Video Profile, Christian Cross Social Foundation